Artificial Intelligence (AI) Solutions In English Language Teaching: Teachers-Students Perceptions And Experiences - Wira Jaya Hartono; Nurfitri Nurfitri; Ridwan Ridwan; Emanuel B S Kase; Floribertha Lake; Rony Sandra Y. Zebua (Departement of Mathematics Education, 2023)
This literature research article explores the perceptions and experiences of teachers and students regarding Artificial Intelligence (AI) solutions in English language teaching. With the rapid advancements in AI technologies, there is a growing interest in leveraging these tools to enhance language learning experiences. Understanding the perspectives of teachers and students is crucial for successful implementation and to harness the potential benefits of AI in the field of English language education. The study adopts a mixed-methods research approach, incorporating both quantitative and qualitative methods. A survey was conducted to gather quantitative data on participants' attitudes, beliefs, and experiences related to AI integration. Additionally, in-depth interviews and focus group discussions were conducted to obtain qualitative insights and delve into participants' perceptions and challenges. The findings of the study reveal positive attitudes towards AI solutions in English language teaching, with participants highlighting the effectiveness of AI technologies in improving language skills and providing personalized instruction. The adaptive nature of AI tools was valued for its ability to cater to individual needs and offer immediate feedback. However, concerns were raised regarding technological readiness and the need for training and support in effectively utilizing AI solutions. These findings have implications for educators, policymakers, and curriculum developers, highlighting the need for technological readiness, teacher training, and support in implementing AI solutions effectively. By embracing the potential of AI while preserving the human element, English language teaching can benefit from personalized and adaptive learning experiences.